Techno-economic and environmental assessment of methane oxidation layer measures through small-scale clean development mechanism – The case of the Seychelles. (1st April 2021) - Cristóbal, Jorge; Sierra, Luis; Margallo, María; Kannengießer, Jan; Aldaco, Rubén; Schebek, Liselotte; Irabien, Ángel
Graphical abstract: Highlights: Coastal landfills in Seychelles are a large source of GHGs and marine debris. Profitability of MOL measures is dependent on SB material existing in the SIDS. Small-scale MOL measures under CDM can be profitable for CER prices of 26 €/tCO2 eq. MOL can be cost-effective for GHG emission abatement from domestic climate efforts. MOL measure contributes to certain SDG achievement – mainly SDG8, SDG13, and SDG14. Abstract: Unclosed coastal landfills in small island developing states are major sources of greenhouse gases and other environmental impacts. This is a major problem for sustainable waste management systems mainly due to the lack of economic resources. The clean development mechanism (CDM) appears as a possibility to facilitate sustainable financing. Implementing a methane oxidation layer (MOL) emerges as a feasible technical option for this kind of small landfills since landfill gas extraction is usually not viable. This paper presents a techno-economic and environmental assessment of MOL implementation in the Providence landfill (Seychelles) as a small-scale CDM measure. Results show that the MOL measure could avoid by 2030 between 94 and 20 kt CO2 eq. Concerning profitability, results clearly show that it depends on the existence of stabilized biomass material within the island. Thus, the MOL measure starts to be profitable in some scenarios for certified emission reductions (CER) prices higher than 26 €/t CO2 eq. that seem possible depending on the emissions' market development. When not profitable under CDM, the MOL measure might be used to reduce CO2 emissions from the domestic climate effort under the Paris Agreement since the unitary abatement costs is between 10 and 423 €/t CO2 eq. Moreover, the MOL measure contributes to the sustainable development goals (SDG) achievement – mainly SDG8, SDG13, and SDG14. Finally, results call for a prompt action in Seychelles since the sooner the MOL is implemented after the landfill is closed, the more profitable.